Nitrogen Fixation by Blue-Green Algal Soil Crusts in Nigerian Savanna - Isichei, A. O. (2014)
Part of this material, in different form, was presented at the Symposium on "The potentials for nitrogen fixation in the tropics", Rio de Janeiro, Brazil, 18-25 July, 1977: "Nitrogen fixation by soil algae of temperate and tropical soils' '. (Stewart, W.D.P., Sampaio, M.J., Isichei, A.O. & Sylvester- Bradley, R.).